SARS-CoV-2 Virus Infection-Related Arterial Thromboembolism Leading to Critical Limb Ischemia and Amputation - Smith, Jenna; Mirza, Aleem; Manunga, Jesse; Skeik, Nedaa (International Journal of Angiology, 2021)
COVID-19 infection has been shown to increase risk for thromboembolism. With most studies reporting mainly venous thromboembolic events, there is a lack of literature regarding the incidence of arterial thromboses in patients with COVID-19 infection. We report a dramatic case of a 55-year-old male with confirmed COVID-19 infection who presented with acute left critical limb ischemia leading to amputation as a result of thromboembolism from a distal abdominal aortic thrombus. Our case report contributes to the limited body of literature on COVID-19-related arterial thromboembolism. The patient consented to publish this case.
Keywords: COVID-19; acute limb ischemia